ҚАЗАҚ ФОЛЬКЛОРЫ АРҚЫЛЫ ЭСТЕТИКАЛЫҚ ТƏРБИЕ БЕРУДІҢ МАЗМҰНЫ. (Journal of Educational Sciences, 2016)
В статье рассматривается значение эстетического воспитания на основе казахского фольклора.The article deals with the meaning of the aesthetic upbringing on the basis of Kazakh folklore.